(untitled) (Journal of the College of Basic Education, 2022)
The current research aimed to identify the effect of the piano on the process of improving the tuning of the tones issued by the violin. The researcher used the experimental approach with the design of two groups (control - experimental) with two pre- and post-tests to achieve the goal of the research, where an experimental sample and another control sample were selected. Each branch consisted of (8) students from the Institute of Fine Arts, Music Department in the city of Khanaqin.The researcher prepared a form (Skillful Performance Evaluation) for male and female students on the topic of tuning the tones on the violin instrument. This form consisted of (8) paragraphs. The results of the study reached the following:A- The students of the experimental group outperformed the students of the control group in the post-skill test.B- The duet playing between (the piano and the violin) was distinguished in improving the tuning of the tones on the violin.